Routledge Handbook of Critical Obesity Studies - Gard, Michael; Powell, Darren; Tenorio, José (Taylor & Francis, 2022)
The Routledge Handbook of Critical Obesity Studies is an authoritative and challenging guide to the breadth and depth of critical thinking and theory on obesity. Rather than focusing on obesity as a public health crisis to be solved, this reference work offers divergent and radical strategies alongside biomedical and positivist discourses.Comprised of thirty nine original chapters from internationally recognised academics, as well as emerging scholars, the Handbook engages students, academics, researchers and practitioners in contemporary critical scholarship on obesity; encourages engagement of social science and related disciplines in critical thinking and theorising on obesity; enhances critical theoretical and methodological work in the area, highlighting potential gaps as well as strengths; relates critical scholarship to new and evolving areas of obesity-related practices, policies and research. This multidisciplinary and international collection is designed for a broad audience of academics, researchers, students and practitioners within the social and health sciences, including sociology, obesity science, public health, medicine, sports studies, fat studies, psychology, nutrition science, education and disability studies.